2009
DOI: 10.1175/2009jhm1061.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Remotely Sensed Actual Evapotranspiration to Improve Rainfall–Runoff Modeling in Southeast Australia

Abstract: This paper explores the use of the Moderate Resolution Imaging Spectroradiometer (MODIS), mounted on the polar-orbiting Terra satellite, to determine leaf area index (LAI), and use actual evapotranspiration estimated using MODIS LAI data combined with the Penman-Monteith equation [remote sensing evapotranspiration (E RS )] in a lumped conceptual daily rainfall-runoff model. The model is a simplified version of the HYDROLOG (SIMHYD) model, which is used to estimate runoff in ungauged catchments. Two application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 29 publications
0
81
2
2
Order By: Relevance
“…Zhang et al 2009 have indicated that calibrations both on ET and streamflow can significant improve the model 0 s capabilities in simulating regional water fluxes and streamflow simulations, particularly over ungauged basins. To enhance DLEM 0 s performance in seasonal streamflow, parameters related to water routing processes, such as the stream flow rate and residential times of lakes, surface and ground water reservoirs, and runoff processes 1901-1978 1979-2008 1901-2008 b 1901-1978 1979-2008 1901-2008 b 1901-1978 1979-2008 1901-2008 1901-1978 and 1979-2008; c The effects of P and T are calculated as the differences in long-term trends between base simulations (i.e., all environmental factors) and experiment of FixP and FixT, respectively.…”
Section: Model Limitationsmentioning
confidence: 99%
“…Zhang et al 2009 have indicated that calibrations both on ET and streamflow can significant improve the model 0 s capabilities in simulating regional water fluxes and streamflow simulations, particularly over ungauged basins. To enhance DLEM 0 s performance in seasonal streamflow, parameters related to water routing processes, such as the stream flow rate and residential times of lakes, surface and ground water reservoirs, and runoff processes 1901-1978 1979-2008 1901-2008 b 1901-1978 1979-2008 1901-2008 b 1901-1978 1979-2008 1901-2008 1901-1978 and 1979-2008; c The effects of P and T are calculated as the differences in long-term trends between base simulations (i.e., all environmental factors) and experiment of FixP and FixT, respectively.…”
Section: Model Limitationsmentioning
confidence: 99%
“…(v) discharge estimation (Callow and Boggs, 2013;Frappart et al, 2005;Kouraev et al, 2004;Smith et al, 1996;Zhang et al, 2004); (vi) evapotranspiration estimation (Donohue et al, 2010;Glenn et al, 2011;Mohamed et al, 2004;Smettem et al, 2013;Zhang et al, 2009);…”
Section: Introductionmentioning
confidence: 99%
“…Remotely sensed soil moisture [Crow and Ryu, 2009;Parajka et al, 2006;Pauwels et al, 2001] and evapotranspiration (or latent heat flux) [Schuurmans et al, 2003;Zhang et al, 2009] can be assimilated into rainfall-runoff models, while remotely sensed snow data Nagler et al, 2008;Slater and Clark, 2006] and brightness temperature [DeChant and Moradkhani, 2011] are used where snowmelt-runoff process is dominant. However, as Pauwels and De Lannoy [2009] pointed out, assimilating remotely sensed data involves converting the remotely sensed signal into state variables either offline or via a built-in observation operator, which is relatively complicated.…”
Section: Introductionmentioning
confidence: 99%